Elite football player engagement with performance analysis - Wright, C.; Carling, C.; Lawlor, C.; Collins, D. (International Journal of Performance Analysis in Sport, 2016)
Despite the wide spread employment of Performance Analysis (PA) within the football coaching process to enhance augmented feedback, until recently little consideration has been given to the context in which PA delivery takes place at elite levels and subsequently impacts on players receiving such information. The aim of this investigation was to explore players' preferred engagement with the PA approach. Comparisons were also drawn between Senior and Academy players. A two phase methodology was employed. 48 male footballers from three English Championship football clubs completed an online questionnaire. Following this 22 players were selected using an opportunistic sample to complete a semi-structured interview. In total, the hierarchical content analysis identified 26 higher order themes and 103 lower order themes. Three key themes emerged and were explored within the discussion: (1) the level of debate and player interaction differed greatly during video feedback sessions, (2) the use of video analysis was central to player self-reflection but the level of engagement with self-reflection varied across players, (3) the majority of players preferred some delay (between 24 and 48 hours) before receiving video feedback. Chi-square statistical analysis identified no meaningful differences in the responses between Senior and Academy players and as a result only descriptive findings were reported. These factors have provided further insight into the practical contexts in which PA is used and perceived by elite players. The most eminent findings have potential implications for coach and analyst education. Further contemplation should be given to the level of interaction during PA feedback as a result of the willingness and ability of a coach to engage a player in discussion regarding their performance and PA use within the player self-reflection process.